Resepsi Video ‘Manisan Belimbing Wuluh Disulap Jadi Kurma' di YouTube 'Dish is Gan' - Samuel Hady Gandojo; Rudy Harjanto; Yunita Sari (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Culinary content using local ingredients has gained popularity on digital platforms, reshaping how audiences respond to culinary innovations using local ingredients. This study aims to share how viewers perceive the cooking video "Manisan Belimbing Wuluh Disulap Jadi Kurma" on the YouTube channel 'Dish is Gan'. Using a qualitative approach with a constructivist paradigm, this study focuses on audiences regarding their social meanings through interactions on digital media, especially YouTube. Analysis of the reception approach with Stuart Hall's coding/decoding theory is used to explore the meanings that shape viewers and their interactions with the content. The method used is an analysis of comments, likes, shares, and video views over a year. The results show that most viewers accept culinary innovations based on starfruit, displaying a dominant position in their reception. Attractive visuals and creative narratives strengthen audience engagement, reflected in increased performance and customer loyalty. However, some viewers are in an oppositional position, especially those unfamiliar with local ingredients. In conclusion, this video successfully builds audience engagement and promotes local culture through digital media, providing insights for content creators to utilize local ingredients to increase audience engagement.